p53: A Regulator of Ferroptosis Induced by Galectin-1 Derived Peptide 3 in MH7A Cells - Hu, Junzheng; Zhang, Rui; Chang, Qing; Ji, Mingliang; Zhang, Haixiang; Geng, Rui; Li, Chao; Wang, Zhen (Frontiers in Genetics, 2022)
Backgrounds: Rheumatoid arthritis synovial fibroblasts (RASFs) are the primary cells responsible for destruction of marginal cartilage in rheumatoid arthritis (RA). G1dP3, a bioactive peptide derived from galectin-1 domain, possesses potent anti-inflammatory and anti-proliferation properties in RASFs. This study aimed to determine the effects of G1dP3 ferroptosis induction in RASFs and to further clarify the possible mechanisms. Methods: TNF-α was used to establish a RA model in MH7A cells. Cell Counting Kit-8 assays were employed to detect MH7A cell viability with different treatments. The occurrence of ferroptosis was examined by Lipid ROS assay, cellular labile iron pool measurement, reduced glutathione/oxidized glutathione activity, Gpx4 expression and transmission electron microscopy (TEM) morphology observation. Lentiviral-mediated siRNA interference was used to determine the downstream pathway. Results: G1dP3 markedly suppressed MH7A cell viability induced by TNF-α. G1dP3-treated MH7A cells presented the morphological features of ferroptosis. Moreover, G1dP3 triggered ferroptosis in MH7A cells by promoting the accumulation of lipid peroxides as well as iron deposition. Inhibition of ferroptosis alleviated G1dP3-mediated suppression of MH7A cell viability. Furthermore, G1dP3 increased p53 expression, which in turn transcriptionally suppressed SLC7A11, a key component of system Xc- essential for ferroptosis. Knockdown of p53 abrogated the ferroptotic effects of G1dP3 on MH7A cells. Conclusion: Our findings reveal that the bioactive peptide G1dP3 promotes RASFs ferroptosis cell death via a p53/SLC7A11 axis-dependent mechanism, suggesting its potential role in the treatment of RA.